Characteristics of tianeptine effects reported to a poison control center: a growing threat to public health. (1st February 2021) - Rushton, William; Whitworth, Brian; Brown, Julie; Kurz, Michael; Rivera, Jessica
Abstract: Background: Tianeptine is an antidepressant structurally similar to tricyclic antidepressants which is approved abroad but is currently a drug of abuse in the United States since at least 2000. In 2019, our poison center experienced an increase in calls relating to this xenobiotic. The goal of this report is to describe the characteristics of acute tianeptine intoxication and withdrawal. Methods: All calls to a statewide poison center regarding tianeptine were reviewed from January 1, 2015 to March 15, 2020. Cases were identified using the American Association of Poison Control Centers' substance code for "other types of tricyclic antidepressants." Cases were excluded if they did not involve tianeptine. Date of call, patient demographics, symptoms, cardiac intervals if available, and disposition were recorded. Results: Eighty-four cases of atypical tricyclic antidepressants were identified in the study period. Forty-eight cases involving tianeptine met inclusion criteria and were reviewed. Of these, 37 (77%) occurred from May 2019 to March 2020. Twenty-seven (56%) required medical admission including 17 cases (35%) that were managed in an intensive care unit. Seventeen of the 48 cases resulted from acute tianeptine intoxication. Lethargy was the most common presentation, but some patients also presented with agitation. Thirty-one (65%) of the cases resulted from tianeptine withdrawal, which usually exhibited agitation, anxiety, gastrointestinal distress. Naloxone was used in 4 cases (24%) of the acute intoxication cohort and benzodiazepines were frequently used both in acutely intoxicated patients and in patients experiencing tianeptine withdrawal. No patients in either cohort had cardiac conduction disturbances. Conclusion: Our center observed a dramatic rise in tianeptine toxicity, particularly in patients experiencing withdrawal symptoms, beginning in May 2019. More than half of the cases required medical admission including a third who were treated in the intensive care unit. Health care practitioners should be increasingly aware of this xenobiotic as usage may be on the rise.